ANALYSIS STRUCTURE THE PT. TEMPO LAND BUILDING - Subhan Manthofani; Arief Firmanto (Journal of Green Science and Technology, 2018)
Mundu  is  an  area  in  the  district of  Cirebon  that  passed  by  the Pantura lane, in the area of the Mundu there are various kinds of  trading industry, one of which is the trading industry from PT.  TEMPO LAND that are producing  medicines  for  health.  In  order  to  create  a  good  production and  marketing, so  in  the  area  is  built  office production  and  marketing  of PT. TEMPO LAND.PT.  TEMPO  LAND  is  a  group  company  in  the  form  of  by  the TEMPO GROUP or PT. TEMPO SCAN PACIFIC Tbk . The company PT. TEMPO GROUP  started  its  business  on  November 3, 1953. Production from this company produces a variety of pharmaceutical and healthcare products with different brands.   In  order  to  create  a  structure  that  is  safe  and  meets serviceability limit, so in the process of design the building structure must be according  to  SNI  - 2847  - 2013  of  reinforced  concrete,  which  is  the latest regulations adapted from the latest material technology development refers to the AISC. Beside planning, the  loading  structure  must  be according to SNI – 1727 – 2013 , then  for  calculation  of  earthquake engineering refers to SNI – 1726 – 2012.Analysis  structure  using  SAP2000,  for  the  material  of  structures  is used  concrete  including  frame  section  (column,  sloof,  beam,  and  slab). And then the  result  from  analysis  are  the  PT.  TEMPO  LAND  building  is safe  or  not,  with  check  the  deflection  and  check  load  maximum  permit from analysis foundation of PT. TEMPO LAND.Keywords : Analysis structure, SAP2000, frame section, deflection.